Factors Influencing Performance of Life Insurance Services in Tanzania: A Case Study of National Insurance Corporation of Tanzania - Deus, Ngaruko D.; Josephine, Mathee T. (Advances in Social Sciences Research Journal, 2014)
The main objective of this study was to identify factors influencing the performance of life insurance service in Tanzania as an effort to contribute and promote insurance sector as an effective catalyst for economic growth. The study was based on data collected from the National Insurance Corporation of Tanzania which covered period of 16 years from 1995 to 2010. Data from annual reports, publications, market performance reports and documentation were obtained. Simple descriptive statistics and graphical analysis were used to describe selected variables. Multiple linear regression analysis was used as sole data analysis methods for research hypotheses. The results show Net Premium Written has been explained by new policies written, the industry market share, the costs of advertisement and marketing, the total number of registered insurance companies, the number of life insurance companies and the early claims settlement.